Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera) VII: Review the genus Apterolarnaca Gorochov, 2004 - Lu, Xiangyi; Zhang, Qianwen; Bian, Xun (Zootaxa, 2022)
Based on the morphology of male ninth abdominal tergite and subgenital plate, this paper redefines the genus Bianigryllacris Cadena-Castañeda, 2019 to subgeneric status under Apterolarnaca Gorochov, 2004. Two species are described as new: Apterolarnaca (Bianigryllacris) tenuispinacia sp. nov. (Chinese name: 细刺缺翅Ô蟋螽) and Apterolarnaca (Bianigryllacris) xinganensis sp. nov. (Chinese name: 兴安缺翅Ô蟋螽). And a key to species of Apterolarnaca is provided. All examined specimens are deposited in Guangxi Normal University.